Adolescents without adolescence: reflections on adolescents’formation of subjectivity and their families in a neoliberal context - Klein, Alejandro (The Spanish Journal of Psychology, 2008)
This study seeks to determine how certain social situations cannot help but influence subjectivity and family ties. The Keynesian age encouraged and promoted a relatively stable socioeconomic matrix based on a probable future and achievable promise. The installation of a family model related to protective parents who were capable of caring for and protecting their children has been observed. Adolescent subjectivity is constructed based on parameters like generational confrontation and growth, and happiness before the possibility of exercising autonomy. On the other hand, neoliberalism produces a “retraction” of social spaces, dismisses the future, and feelings of instability and insecurity are prevalent, making the family model a “structure that overwhelms parents.” Adolescent subjectivity seems incapable of executing generational confrontation, predominantly showing a desire to “protect” the family (“exacerbated messiah complex”) by means of a fantasy that acts as a “threading scene” capable of annulling the search for autonomy and growth.